1998
DOI: 10.1159/000030911
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Contamination of Autologous Bone Marrow: Reinfusion of& ;Culture-Positive Grafts Does Not Result in Clinical Sequelae during the Posttransplantation Course

Abstract: Objectives: Microbiological cultures and posttransplantation course were analyzed in order to investigate the incidence and clinical significance of bacterial contamination of autologous bone marrow (BM) grafts. Methods: Cultures were obtained from BM after collection, BM concentrate after processing, contaminated/cryopreserved BM at thawing, and from peripheral blood (PB) following autologous BM transplantation (ABMT). The posttransplantation course of patients grafted with culture-positive BM was recorded an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
6

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 38 publications
3
34
0
6
Order By: Relevance
“…Some authors reported that they did not recover CNS from contaminated products after they were cryopreserved and subsequently thawed, while other authors stated that CNS can survive the cryopreservation and thawing procedures. 8,11,14 In our series, we found 5 products, among 13, which had positive cultures for CNS before cryopreservation and remained positive after thawing -making it important to take into account a positive culture before cryopreservation, when discussing antibiotic therapy.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Some authors reported that they did not recover CNS from contaminated products after they were cryopreserved and subsequently thawed, while other authors stated that CNS can survive the cryopreservation and thawing procedures. 8,11,14 In our series, we found 5 products, among 13, which had positive cultures for CNS before cryopreservation and remained positive after thawing -making it important to take into account a positive culture before cryopreservation, when discussing antibiotic therapy.…”
Section: Discussionmentioning
confidence: 84%
“…All autologous transplant patients had neutrophil recovery at a median of 10 days (range, [8][9][10][11][12][13][14]. Among the allogeneic transplant patients, all but one engrafted in a median of 13 days (range, 5-21).…”
Section: (8%)mentioning
confidence: 99%
See 1 more Smart Citation
“…En algunos de estos estudios, se han realizado comparaciones en el curso post trasplante de pacientes que recibieran cosechas de médula ósea contaminadas y no contaminadas. Aquellos pacientes infundidos con cosechas contaminadas no mostraron diferencias importantes con pacientes que recibieron médula ósea no contaminada, en cuanto a tiempo de reconstitución hematopoyética, días febriles y/o días con antimicrobianos 40,41 .…”
Section: Conducta Frente a Un Cultivo Positivounclassified
“…This is completely different for a cell therapy product where volume available is very small, and the concentration of germs, if 85 there are, very low. At the time of implementation, based growth methods with rich medium as those for blood culture were used for the control of labile blood products (Brecher et al, 2001;McDonald et al, 2001;Dunne et al, 2005) as for bone marrow control (Schwella et al, 1998). Taking together, it was decided to evaluate an automated blood culture system for the microbiological control of cell therapy products.…”
Section: Introductionmentioning
confidence: 99%